2014
DOI: 10.1155/2014/917212
|View full text |Cite
|
Sign up to set email alerts
|

Fumigation Toxicity of Essential Oil Monoterpenes to Callosobruchus maculatus (Coleoptera: Chrysomelidae: Bruchinae)

Abstract: The fumigant toxicity of eight essential oil components, 1-8-cineole, carvacrol, eugenol, (−)-menthone, (−)-linalool, S-(−)-limonene, (−)-β-pinene, and (+)-α-pinene, was tested against the cowpea weevil,Callosobruchus maculatus(Fabricius) (Coleoptera: Chrysomelidae), at 0.25–60 µL/L air doses. 1-8-Cineole, carvacrol, and eugenol caused complete adult mortality at 10 µL/L air 24 h after treatment. 1-8-Cineole and carvacrol were the most toxic with LD50values of 0.24 and 0.6 µL/L air at 24 h, respectively. (−)-β… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 28 publications
0
16
0
2
Order By: Relevance
“…The essential oil of Salvia leriifolia Benth (Lamiaceae) showed the highest insecticidal activity as fumigant and contact agents against adults of C. maculatus, S. oryzae, and T. castaneum [100]. It was indicated that among eight terpenes including 1,8-cineole, carvacrol, eugenol, menthone, linalool, limonene, β-pinene, and α-pinene, the cyclic monoterpenoids carvacrol and menthone had the most fumigant toxicity against the cowpea weevil, C. maculatus [101]. In another study, the fumigant and contact toxicities of eugenol (a phenylpropanoid), ρ-cymene and α-pinene (monoterpenes), and menthone, α-terpinene, and terpinen-4-ol (monoterpenoids) were evaluated against T. castaneum adults.…”
Section: Chemical Composition Of Essential Oils and Their Relative Pementioning
confidence: 99%
“…The essential oil of Salvia leriifolia Benth (Lamiaceae) showed the highest insecticidal activity as fumigant and contact agents against adults of C. maculatus, S. oryzae, and T. castaneum [100]. It was indicated that among eight terpenes including 1,8-cineole, carvacrol, eugenol, menthone, linalool, limonene, β-pinene, and α-pinene, the cyclic monoterpenoids carvacrol and menthone had the most fumigant toxicity against the cowpea weevil, C. maculatus [101]. In another study, the fumigant and contact toxicities of eugenol (a phenylpropanoid), ρ-cymene and α-pinene (monoterpenes), and menthone, α-terpinene, and terpinen-4-ol (monoterpenoids) were evaluated against T. castaneum adults.…”
Section: Chemical Composition Of Essential Oils and Their Relative Pementioning
confidence: 99%
“…For example, the extract of Carica papaya yielded 46% mortality in S. oryzae after 72 hr of treatment when added to the diet, but the same extract as a vapor caused almost 100% mortality of these insects. As the data of studies conducted by Ajayi, Appel, and Fadamiro () show, components of essential oils, such as 1‐8‐cineole, carvacrol, and eugenol, also possess a high fumigant toxic activity against the cowpea weevil C. maculatus , causing ≥90% mortality of adult beetles at low doses of 5 μL/L of air within 24 hr. Similar results were obtained by (Bett et al., ), who tested leaf essential oils from C. lusitanica and E. saligna against A .…”
Section: Applicationmentioning
confidence: 99%
“…It was found that at the highest tested dose (60 μL/L) 1‐8‐cineole and carvacrol completely deterred oviposition. Among the oil treatments in lower doses that did not completely prevent oviposition, the tested essential oils completely inhibited adult emergence (Ajayi et al., ).…”
Section: Applicationmentioning
confidence: 99%
“…The highly toxic and repellent effects of main constituents of these oils, camphor and linalool, have been demonstrated by other researchers (Chen et al, 2013;Ajayi et al, 2014). Linalool was shown to exhibit fumigant toxicity against S. zeamais (Wang et al 2011;Liu et al, 2013;Yildirim et al, 2013) and the C. camphora, with camphor as major component, showed repellent activity (Liu et al, 2006) and high insecticidal activity against S. oryzae (Hamed et al, 2012).…”
Section: Repellencymentioning
confidence: 89%